2012
DOI: 10.1021/jf3024744
|View full text |Cite
|
Sign up to set email alerts
|

Ionome of Soybean Seed Affected by Previous Cropping with Mycorrhizal Plant and Manure Application

Abstract: Two field experiments were conducted to investigate the effects of previous cultivation of an arbuscular mycorrhizal (AM) host plant and manure application on the concentration of 19 mineral elements in soybean ( Glycine max L. Merr. cv. Tsurumusume) seeds. Each experiment ran for two years (experiment 1 took place in 2007-2008, and experiment 2 took place in 2008-2009) with a split plot design. Soybeans were cultivated after growing either an AM host plant (maize, Zea mays L. cv. New dental) or a non-AM ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
(72 reference statements)
2
31
0
Order By: Relevance
“…The increase in the low‐molecular‐weight organic acids released from manure and those secreted by the roots are hypothesized to have promoted the direct uptake and upward translocation of heavy metals because organic acids can increase the chelation and solubility of heavy metal ions ( Strickland et al, 2015). We previously reported that the M treatment increased the Cd and Ba concentrations of soybean seeds ( Sha et al, 2012). The increase in Ba and Sr concentrations of shoots were likely related to the Ca and Mg metabolism, because Mg, Ca, Sr and Ba are chemically similar and share translocation pathways ( Watmough , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the low‐molecular‐weight organic acids released from manure and those secreted by the roots are hypothesized to have promoted the direct uptake and upward translocation of heavy metals because organic acids can increase the chelation and solubility of heavy metal ions ( Strickland et al, 2015). We previously reported that the M treatment increased the Cd and Ba concentrations of soybean seeds ( Sha et al, 2012). The increase in Ba and Sr concentrations of shoots were likely related to the Ca and Mg metabolism, because Mg, Ca, Sr and Ba are chemically similar and share translocation pathways ( Watmough , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The ionome is defined as all the mineral nutrients and trace elements found in an organism ( Salt et al, 2008). For crops, the ionome has predominantly been studied in soil, plant seeds or shoots to determine the nutritional status of plants ( Vohland et al, 2009; Sha et al, 2012; Chu et al, 2015; Pii et al., 2015). However, there is little information on the elemental composition of below‐ground parts, especially for legume crops with nodules.…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation was also found between the chemically similar elements K and Na, but this correlation was not significant in previous studies (Baxter et al, 2012;Sha et al, 2012). Given that this correlation was previously analyzed on the basis of variation under different cultivation conditions, the absence of significance could have been due to a difference in the response to such cultivation conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Ionomes of edible parts have been reported for rice and soybean (Norton et al, 2010;Sha et al, 2012). In soybean, dried mature seeds are used, and there are no reports of ionome analysis using immature soybean as a vegetable, edamame, as described in the present study.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation